How Do Financial Experts Choose Stocks? - Gesti Memarista; Melisa Kusuwati (Universitas Airlangga, 2022)
Objective: This study aims to determine factors that affect financial experts as investors to buy stocks. Do financial experts have different considerations and preferences from ordinary investors in making an investment decision? Design/Methods/Approach: The research data were obtained from an online questionnaire by 581 financial experts with Securities Sub Account in Indonesian Central Securities Depository. This research employs exploratory factor analysis to examine the correlation between 29 attribute statements to develop factors. Findings: The eight groups of factors that affect the Indonesian financial expert's considerations in the stock investment such as financial performance, comprehensive analysis, benefit signaling, company image, company insight, community involvement, investor preference, and press coverage. Originality: This study incorporates behavioral finance and maximization utility to provide a more comprehensive understanding of stock investment decisions by financial experts. Practical/Policy implication (optional): The result has practical, functional consequences for the investor, especially in the selected stock portfolio analysis. Investment analysis should consider the eight groups of factors found before choosing the stock. If the investors can not assume all factors, they can view the financial performance as the top rank factor. Thus the investor will maximize the investment return in the future.